GRACILARIA SPECIES (GRACILARIALES, RHODOPHYTA) OF MALAYSIA INCLUDING TWO NEW RECORDS - Phaik-Eem, Lim; Siew-Moi, Phang (Malaysian Journal of Science, 2004)
The west coast Peninsular Malaysia is dominated by mangrove swamps, which provide a natural habitat for Gracilaria species to grow. To date, twenty species of Gracilaria and one species of Gracilariopsis have been collected in Malaysia. There are many other areas yet to be surveyed for other Gracilaria species. Two new records of Gracilaria: Gracilaria articulata Chang et Xia and Gracilaria manilaensis Yamamoto et Trono collected for the first time in the west coast of Peninsular Malaysia, are described.